Design, Shopping Centers and the Scale of Tendency and Feelings Of Consumers Toward Entrance (Philosophy Of Design)Diversity And Fast Change Of Constituents Of Modern Life Due To The Advertising Skills And Techniques With An Artistic Approach Have Led To - Seyed Rahmatollah Mousavimoghadam, Zeinab Arab (International Journal of Modern Agriculture, 2021)
Diversity And Fast Change Of Constituents Of Modern Life Due To The Advertising Skills And Techniques With An Artistic Approach Have Led To The Change Of Life Style Of Many Of Consumers To The Extent That The Necessity Of Consumption And Freedom In Choice Has Fallen Victim To Immediate And Superficial Impact Of Advertisement And Artistic Resources And The Role Of Will And Power Of Choice Or Denial In Modern Man Remains Passive; The Expansion Of This Technique And Power Of Art And Design With Two Positive And Negative Approaches Have Doubled The Necessity Of Research In This Regard And Thus Paying Attention To "Philosophy Of Design" Seems To Be Unavoidable In Modern World. Materials And Methods: The Method Of The Current Study Is Applied And Survey Type; The Statistical Society Of This Research Is Consisted Of The Citizens Of Sari City From Whom 386 Men Have Been Selected Using Random Sampling Method And By Means Of Morgan’s Table. Findings: Emotional Conception And Initial Encounter Of Consumers Of/With The Design Of The Front And Show Window Of Stores Influence Their Behavior To A Considerable Extent. Environmental Graphic Factors Of The Front And Show Window Of Shopping Centers Are Very Influential On The Behaviors Of Consumers; Audio And Visual Elements Used In The Front And Show Windows Of The Stores Orient The Behavior Of Consumers; The Color And Light Used In The Front And Show Windows Of The Stores Also Have An Influence On The Decisions And Emotions Of Consumers. Conclusion: To Increase The Attraction And Even For Making This Type Of Centers More Peaceful For The Consumers And Also For Better Management Of The Mind And Thought Of The Consumers Through "Tourism", Which Is Today The Foundation Of National Economy Of Many Countries, Design Is A Key And Strategic Commercial Category In Enhancing The Sense Of Satisfaction In Viewers With Its Focus On "Environmental Graphic" And Attractive Points; Environmental Graphic Which Represents The Most Symbolic Part Of Design Is An Applied And Economic Art; Because It Immediately Becomes Related With Human Sight And Mind And Plays An Effective Role In Creation Of A Peaceful Space For Individuals And Constitutes One Of The Foundations Of "Art Economy".